1989
DOI: 10.1115/1.3168381
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Mucus Clearance in Cough

Abstract: An instability resembling an avalanche is proposed as the mechanism by which mucus is expelled from the respiratory tract during cough. The cough event was simulated in a model airway. In these experiments, air was forced through a channel whose walls were lined with a non-Newtonian material rheologically similar to tracheal mucus. Frames from high-speed cine photographs showed an unstable event which began as an undulation of the free surface and progressed to a catastrophic clearance of the channel. Measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 0 publications
6
51
0
Order By: Relevance
“…Phasic Motion (Shear Stress) Culture Conditions; Normal Versus CF Bronchial Epithelial PCL Volume Regulation-Breathing imparts shear on pulmonary surfaces by airflow-induced shear stress, cyclic compressive (transmural) shear, and stretch (13). However, calculation of total shear-stress on pulmonary surfaces has been difficult, and comprehensive model systems are unavailable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phasic Motion (Shear Stress) Culture Conditions; Normal Versus CF Bronchial Epithelial PCL Volume Regulation-Breathing imparts shear on pulmonary surfaces by airflow-induced shear stress, cyclic compressive (transmural) shear, and stretch (13). However, calculation of total shear-stress on pulmonary surfaces has been difficult, and comprehensive model systems are unavailable.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the observations that (i) tidal volume expansion and airflow impart shear to airway surfaces (13), (ii) shear releases nucleotides from many cell types into the extracellular environment (14,15), and (iii) extracellular nucleotides interact with P2Y 2 and P2X purinoceptors to regulate airway ion transport (16,17), we hypothesized that the failure to recapitulate in vitro the phasic motion associated with tidal breathing has hindered the identification of the pathways for PCL volume autoregulation. Accordingly, we developed a novel culture system that mimics the best characterized shear stress in the lung, i.e.…”
mentioning
confidence: 99%
“…Consistent with this thesis are previous studies which have reported that ATP is released from human airway epithelia subjected to physical forces. This includes forces generated by mechanical deformation (Kallok et al, 1983;Grygorczyk et al, 1997;Homolya et al, 2000;Knight et al, 2002), fluid shear stress (Grierson et al, 1995;Guyot et al, 2002;Lazarowski et al, 2004;Tarran et al, 2005), compression/stretch (Basser et al, 1989;Button et al, 2007), osmotic shock (Mitchell et al, 1998;Okada et al, 2006), or by simply changing of the media of cultured cells .…”
Section: Stress-stimulated Atp Releasementioning
confidence: 99%
“…4 The mucus is a nonNewtonian fluid 5 that exhibits viscoelastic and shear thinning characteristics, and possesses a yield stress. 6,7 In the terminal bronchioles, beyond generation 17, there is essentially a single fluid layer whose viscous properties are similar to those of water.…”
Section: Introductionmentioning
confidence: 99%